Method for manufacturing solid-state battery

JP2025021693APending Publication Date: 2025-02-14FDK CORP

Patent Information

Application Number
JP2023125597
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-01
Publication Date
2025-02-14

AI Technical Summary

Benefits of technology

【0008】 1つの側面では、耐酸化性に優れた固体電解質を含む固体電池を実現することが可能になる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025021693000001_ABST
    Figure 2025021693000001_ABST
Patent Text Reader

Abstract

To provide a solid-state battery which is excellent in oxidation resistance and includes a solid electrolyte.SOLUTION: A solid-state battery 1 includes a positive electrode layer 11, a negative electrode layer 12, and an electrolyte layer 13 provided therebetween, and in at least one of these layers, a solid electrolyte is used. A method for manufacturing the solid-state battery 1 includes steps of: preparing an amorphous solid electrolyte material having a NASICON type structure; and firing the amorphous solid electrolyte material in a temperature range of 600°C or higher and lower than 800°C and forming a solid electrolyte including a crystalline phase and an amorphous phase from the amorphous solid electrolyte material. In the solid electrolyte thus formed, oxidative decomposition under a positive electrode side voltage can be effectively suppressed.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a solid-state battery. [Background technology]

[0002] A technique is known in which a lithium ion conductive solid electrolyte mainly made of sulfide is used as the electrolyte for an all-solid-state lithium battery, and the surface of the positive electrode active material is coated with an amorphous lithium ion conductive oxide (Patent Document 1).

[0003] Also, a technology is known that uses a solid electrolyte that contains Li (lithium), P (phosphorus), S (sulfur), and O (oxygen) as the electrolyte for an all-solid-state lithium battery, and that is neither amorphous nor thermodynamically stable crystalline, but is a thermodynamically non-equilibrium crystalline solid electrolyte that is intermediate between the two (Patent Document 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2007 / 004590 Brochure [Patent Document 2] JP 2007-305552 A Summary of the Invention [Problem to be solved by the invention]

[0005] Incidentally, a solid-state battery using an oxide-based solid electrolyte having a NASICON (Na super ionic conductor) type structure is known. In a solid electrolyte having a NASICON type structure, lithium ion conductivity is exhibited by crystallization caused by firing. On the other hand, in a solid electrolyte having a NASICON type structure, oxidative decomposition may occur under the positive electrode voltage of the solid-state battery. The oxidative decomposition of the solid electrolyte may cause deterioration of the characteristics of the solid-state battery.

[0006] In one aspect, the present invention aims to provide a solid-state battery including a solid electrolyte having excellent oxidation resistance. [Means for solving the problem]

[0007] In one embodiment, a method for producing a solid-state battery is provided, the method including the steps of: preparing an amorphous solid electrolyte material having a NASICON-type structure; and sintering the amorphous solid electrolyte material at a temperature range of 600° C. or more and less than 800° C. to form a solid electrolyte including a crystalline phase and an amorphous phase from the amorphous solid electrolyte material. Effect of the Invention

[0008] In one aspect, it becomes possible to realize a solid-state battery that includes a solid electrolyte that has excellent oxidation resistance. [Brief description of the drawings]

[0009] [Figure 1] 1A to 1C are diagrams illustrating an example of a method for manufacturing a solid-state battery. [Diagram 2] FIG. 13 is a diagram showing an example of an LSV measurement result. [Diagram 3] FIG. 1 is a diagram showing an example of an X-ray diffraction measurement result. [Figure 4] FIG. 13 is a diagram showing an example of a Raman spectroscopy measurement result. [Diagram 5] FIG. 13 is a diagram showing an example of an appearance observation result. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] First, an example of a method for manufacturing a solid-state battery will be described. Fig. 1 is a diagram for explaining an example of a method for manufacturing a solid-state battery. Fig. 1(A) shows a schematic cross-sectional view of a main part of an example of a battery element forming step. Fig. 1(B) shows a schematic cross-sectional view of a main part of an example of an external electrode forming step.

[0011] First, a battery element 10 as shown in FIG. 1(A) is formed. The battery element 10 is an example of a power generation element of a lithium-ion secondary battery. The battery element 10 includes a positive electrode layer 11, a negative electrode layer 12, an electrolyte layer 13, and a cover layer 14. The positive electrode layer 11 and the negative electrode layer 12 are laminated so as to partially overlap each other with the electrolyte layer 13 interposed therebetween. A cover layer 14 is provided so as to cover a laminate including the positive electrode layer 11 and the negative electrode layer 12 and the electrolyte layer 13 provided therebetween. A part of the side surface of the positive electrode layer 11 is provided so as to be exposed at one end face 10a of the battery element 10, and a part of the side surface of the negative electrode layer 12 is provided so as to be exposed at the other end face 10b of the battery element 10. Note that the number of layers of the positive electrode layer 11, the negative electrode layer 12, and the electrolyte layer 13 of the battery element 10 shown in FIG. 1(A) is an example and is not limited to the number of layers shown in FIG. 1(A).

[0012] The electrolyte layer 13 contains a solid electrolyte. For example, an oxide-based solid electrolyte having a NASICON-type structure is used as the solid electrolyte of the electrolyte layer 13. For example, as the solid electrolyte of the electrolyte layer 13, LAGP represented by the general formula Li 1+x Al x Ge 2-x (PO4)3 (0 < x ≤ 1) is used. As an example of LAGP, Li 1.5 Al 0.5 Ge 1.5 (PO4)3 having a composition of x = 0.5 is used as the solid electrolyte of the electrolyte layer 13.

[0013] The positive electrode layer 11 contains a positive electrode active material, a conductive assistant, and a solid electrolyte. For example, an oxide-based solid electrolyte having a NASICON-type structure is used as the solid electrolyte of the positive electrode layer 11. As the solid electrolyte of the positive electrode layer 11, for example, the same material as the solid electrolyte of the electrolyte layer 13, here, LAGP as described above is used. For example, Li2CoP2O7 (lithium cobalt pyrophosphate, also referred to as "LCPO") is used as the positive electrode active material of the positive electrode layer 11. For example, a conductive material such as carbon is used as the conductive assistant of the positive electrode layer 11.

[0014] The negative electrode layer 12 includes a negative electrode active material, a conductive assistant, and a solid electrolyte. For example, an oxide-based solid electrolyte having a NASICON structure is used for the solid electrolyte of the negative electrode layer 12. For example, the same material as the solid electrolyte of the electrolyte layer 13, such as the above-mentioned LAGP, is used for the solid electrolyte of the negative electrode layer 12. For example, TiO2 (titanium oxide) or Nb2O5 (niobium pentoxide) is used for the negative electrode active material of the negative electrode layer 12. For example, a conductive material such as carbon is used for the conductive assistant of the negative electrode layer 12.

[0015] In the battery element 10, during charging, lithium ions are conducted from the positive electrode layer 11 through the electrolyte layer 13 to the negative electrode layer 12 and are incorporated therein, and during discharging, lithium ions are conducted from the negative electrode layer 12 to the positive electrode layer 11 through the electrolyte layer 13 and are incorporated therein. In the battery element 10, charging and discharging operations are realized by such lithium ion conduction.

[0016] As the cover layer 14, for example, an insulating cover layer 14 is used which has a higher hardness than the solid electrolytes used in the positive electrode layer 11, the negative electrode layer 12, and the electrolyte layer 13, has low permeability to moisture, etc., and can realize good sealing. The insulating property of the cover layer 14 refers to a property that has no or sufficiently low influence on the lithium ion conduction and electron conduction in the battery element 10. The cover layer 14 is made of a solid electrolyte, glass, ceramics, or the like.

[0017] In forming the battery element 10, pastes for forming the positive electrode layer 11, the negative electrode layer 12, the electrolyte layer 13, and the cover layer 14, each containing the material components as described above, are prepared. Then, each paste is laminated by printing to form a structure as shown in FIG. 1(A), or sheets formed from each paste by printing are laminated to form a structure as shown in FIG. 1(A). After lamination, thermocompression bonding, cutting, and the like may be performed. Then, a predetermined heat treatment, that is, a heat treatment (also called "degreasing") for removing organic components in the paste, and further a heat treatment (also called "firing") for sintering the solid electrolyte, glass, and the like are performed. As a result, the battery element 10 having the structure shown in FIG. 1(A), that is, the battery element 10 including the positive electrode layer 11, the negative electrode layer 12, the electrolyte layer 13, and the cover layer 14, is formed.

[0018] After the battery element 10 is formed, the external electrode 20 and the external electrode 30 are formed as shown in FIG. 1(B). The external electrode 20 is formed on one end surface 10a of the battery element 10 so as to be connected to the positive electrode layer 11 exposed on the end surface 10a. The external electrode 20 functions as the positive electrode of the solid-state battery 1. The external electrode 30 is formed on the other end surface 10b of the battery element 10 so as to be connected to the negative electrode layer 12 exposed on the end surface 10b. The external electrode 30 functions as the negative electrode of the solid-state battery 1. Various conductive materials are used for the external electrodes 20 and the external electrodes 30. For example, the external electrodes 20 and the external electrodes 30 are made by applying and baking a paste containing metals such as Ag (silver) and Cu (copper) or conductive particles such as carbon, or by further forming a metal such as Ni (nickel) or Sn (tin) on the surface by plating or the like.

[0019] By the above-described method, a solid-state battery 1 is manufactured, which includes a battery element 10 including a positive electrode layer 11, a negative electrode layer 12, an electrolyte layer 13, and a cover layer 14, as well as an external electrode 20 and an external electrode 30 provided on the end surface 10a and the end surface 10b, respectively.

[0020] Incidentally, a solid electrolyte having a NASICON structure such as LAGP used in the above-mentioned solid battery 1 is likely to have high lithium ion conductivity when it becomes crystalline, and usually, by being crystallized by firing, a certain level or more of lithium ion conductivity is expressed. In addition, a positive electrode active material such as LCPO used in the above-mentioned solid battery 1 is known as one of the materials that can increase the operating voltage on the positive electrode side and increase the operating voltage of the solid battery 1 (the operating voltage difference between the positive and negative electrode sides). However, a solid electrolyte having a NASICON structure such as the above-mentioned LAGP, which is included in the solid battery 1 together with such a positive electrode active material such as LCPO, may undergo oxidative decomposition under a relatively high positive electrode side voltage of the solid battery 1.

[0021] Therefore, the crystallinity, lithium ion conductivity, oxidative decomposition property, etc. of the solid electrolyte used in the solid-state battery 1 were evaluated. More specifically, amorphous solid electrolyte materials having a NASICON-type structure were prepared, and the physical properties such as ion conductivity, oxidative decomposition behavior, material structure (crystallinity), etc. were evaluated when the materials were fired under various conditions. For the evaluation, amorphous solid electrolyte materials before firing were amorphous LAGP (Li 1.5 Al 0.5 Ge 1.5 (PO4)3) was used. This evaluation is explained below.

[0022] [Preparation of amorphous LAGP] First, the raw materials for LAGP, Li2CO3 (lithium carbonate), Al2O3 (aluminum oxide), GeO2 (germanium oxide), and NH4H2PO4 (ammonium dihydrogen phosphate), were weighed out to a specified composition ratio and mixed in a magnetic mortar or ball mill. The mixture obtained by mixing was placed in an alumina crucible and pre-fired at 300 to 400°C for 3 to 5 hours. The powder obtained by pre-fire was melted by heat treatment at 1200 to 1400°C for 1 to 2 hours. The material obtained by melting was rapidly cooled and vitrified to obtain amorphous LAGP powder.

[0023] The amorphous LAGP powder thus obtained was roughly crushed to a particle size of 200 μm or less, and then further crushed using a crushing device such as a ball mill to adjust the particle size d (median size) to the desired value. As an example, the particle size p of the amorphous LAGP powder was adjusted to the range of 2 μm≦d≦5 μm.

[0024] [Preparation of amorphous LAGP paste and sheet] First, 20wt% to 30wt% of a binder such as PVDF (polyvinylidene fluoride) was added to the amorphous LAGP powder described above, and 30wt% to 50wt% of anhydrous alcohol such as anhydrous isopropanol was added as a solvent to the amorphous LAGP powder. This resulted in a paste-like raw material containing the amorphous LAGP powder. The raw material obtained was then mixed in a ball mill for 20 hours to be homogenized. This resulted in an amorphous LAGP paste containing the amorphous LAGP powder.

[0025] The obtained amorphous LAGP paste was degassed in a vacuum, and then the amorphous LAGP paste was coated on a PET (polyethylene terephthalate) film by a doctor blade method and formed into a sheet. In this case, if a predetermined sheet thickness is obtained, coating may be performed once, or coating may be repeated multiple times to obtain a predetermined sheet thickness. In addition, multiple sheets obtained by one or multiple coatings may be laminated to obtain a predetermined sheet thickness. The sheet having a predetermined sheet thickness was thermocompressed, and the thermocompressed sheet was cut into a predetermined planar size to obtain an amorphous LAGP sheet containing amorphous LAGP powder.

[0026] As an example, an amorphous LAGP sheet with a thickness of 300 μm and a planar size of 20 mm × 20 mm was obtained using an amorphous LAGP paste with a composition ratio of amorphous LAGP powder:PVDF:anhydrous isopropanol = 20 wt%:30 wt%:50 wt%.

[0027] [Firing] The obtained amorphous LAGP sheet was placed on a honeycomb-shaped sintered plate and sintered under the conditions of a predetermined sintering temperature (holding temperature), sintering atmosphere, and sintering time (holding time) to obtain a LAGP sintered body. Here, the following LAGP sintered bodies of Samples No. 1-7 were obtained.

[0028] As sample No. 1, a LAGP sintered body was obtained by sintering at 600°C in a nitrogen atmosphere for 2 hours. As sample No. 2, a LAGP sintered body was obtained by sintering at 600°C in air for 2 hours.

[0029] As sample No. 3, a LAGP sintered body was obtained by sintering at 700°C in air for 2 hours. As sample No. 4, a LAGP sintered body was obtained by sintering at 700°C in air for 20 hours.

[0030] As sample No. 5, a LAGP sintered body was obtained by sintering at 800°C in air for 2 hours. As sample No. 6, a LAGP sintered body was obtained by sintering at 900°C in air for 2 hours.

[0031] Also, as sample No. 7, a LAGP sintered body was obtained by sintering at 780°C in air for 2 hours. The obtained LAGP sintered body was used in a test cell, X-ray diffraction measurement, Raman spectroscopy measurement, appearance observation, and the like, which will be described later.

[0032] [Preparation of test cell] One side of the obtained LAGP sintered body was coated with Au (gold) to form an electrode. After vacuum drying at 150°C for 12 hours in a glove box dryer, Li metal was provided on the other side of the LAGP sintered body via a polymer electrolyte, and Li metal was cut into 22 mm squares and Cu foil was attached as the counter electrode. This was enclosed in a laminate film exterior to form a test cell. The test cell was used for impedance measurement and LSV (linear sweep voltammetry) measurement, which will be described later.

[0033] [Impedance measurement] The obtained test cell was placed in a thermostatic chamber set at 23° C., and impedance measurement was performed using an impedance measuring device in a frequency range of 0.1 Hz to 1 MHz with an amplitude of 0.5 mV.

[0034] [LSV measurement] The obtained test cell was placed in a thermostatic chamber set at 23° C., and LSV measurement was performed using an impedance measuring device at a sweep rate of 1 mV / sec in a voltage range of 3 V to 6 V.

[0035] [X-ray diffraction measurement] The obtained LAGP sintered body was subjected to X-ray diffraction measurement using an X-ray diffractometer with Cu Kα radiation (Cu-Kα) in the diffraction angle 2θ range of 10° to 50°.

[0036] [Raman spectroscopy measurement] The obtained LAGP sintered body was subjected to Raman spectroscopy measurement using a laser microscopic Raman spectrometer with a laser having a wavelength of 453 nm under the conditions of an exposure time of 1 second, an accumulation number of 4, a neutral density filter of 50%, and a measurement time of 40 minutes.

[0037] [Appearance Observation] The appearance of the obtained LAGP sintered body was observed using a microscope. 〔evaluation〕 The LAGP sintered compacts of samples No. 1-6 were obtained by sintering amorphous LAGP sheets with a sheet thickness of 300 μm and a plane size of 20 mm × 20 mm under various conditions. From the results of impedance measurements of test cells using these LAGP sintered compacts, the bulk resistance Rs [Ω], interface resistance Rp [Ω], and ionic conductivity [S / cm] of the LAGP sintered compacts were obtained. In addition, the sintered density [%] of the LAGP sintered compacts of samples No. 1-6 was obtained. The results are shown in Table 1.

[0038] [Table 1]

[0039] First, among Samples No. 1-6 shown in Table 1, attention will be focused on Sample No. 1-5, which was fired at a temperature of less than 900° C. Sample No. 6 will be described later. From Table 1, it can be seen that for the LAGP sintered compacts of samples No. 1-5, the ionic conductivity tends to increase with increasing sintering temperature and time. Also, for the LAGP sintered compacts of samples No. 1-5, the sintered density tends to increase with increasing sintering temperature and time. Also, of the bulk resistance Rs and interface resistance Rp of the LAGP sintered compacts of samples No. 1-5, the interface resistance Rp tends to decrease with increasing sintering temperature and time.

[0040] It is considered that the crystallization of the LAGP sintered body of Sample No. 1-5 advances with an increase in the sintering temperature and the sintering time, and the ionic conductivity of the LAGP sintered body increases. -5 Even in sample No. 1-2, which had the lowest firing temperature of 600°C, the -5 Ionic conductivities on the order of S / cm can be obtained.

[0041] LAGP with ionic conductivity of this order can be fully utilized as the solid electrolyte used in the electrolyte layer 13 of the solid-state battery 1, or the solid electrolyte used in the positive electrode layer 11 or the negative electrode layer 12. Therefore, the firing temperature during firing of the LAGP (battery element 10 including the LAGP) performed during the manufacture of the solid-state battery 1 can be set to, for example, a firing temperature in the range of 600° C. or higher and 800° C. or lower, as in Sample No. 1-5.

[0042] Here, the LAGP used in the solid-state battery 1 may come into contact with LCPO, which is the positive electrode active material of the positive electrode layer 11, due to the arrangement of the positive electrode layer 11 and the electrolyte layer 13 or the configuration of the positive electrode layer 11. In such a state of contact with the LCPO, the LAGP may react with the LCPO during firing performed in the manufacture of the solid-state battery 1. From the viewpoint of suppressing such a reaction between the LAGP and the LCPO during firing and the resulting decomposition of the LAGP and the LCPO, and from the viewpoint of suppressing the oxidative decomposition of the LAGP during the operation of the solid-state battery 1 as described below, it is preferable that the firing temperature of the LAGP (battery element 10 including the LAGP and the LCPO) is low, and it is more preferable to set the firing temperature to a relatively low temperature below 800° C., such as 600° C. or 700° C. as in sample No. 1-4.

[0043] Next, sample No. 6 will be described. From Table 1, the LAGP sintered body of sample No. 6, which was sintered at 900°C, has a lower ionic conductivity than the LAGP sintered body of sample No. 5, which was sintered at 800°C, despite the higher sintering temperature. This is thought to be because, when the sintering temperature rises to 900°C, as in the case of the LAGP sintered body of sample No. 6, LAGP crystallizes, and melts and voids form, reducing the conduction path of lithium ions. From the results shown in Table 1, when the sintering temperature rises to 900°C, as in the case of the LAGP sintered body of sample No. 6, the sintered density falls compared to the LAGP sintered body of sample No. 5, which was sintered at 800°C, and the bulk resistance Rs and interface resistance Rp rise. When the sintering temperature rises to 900°C, as in the case of the LAGP sintered body of sample No. 6, there is a concern that the reaction between LAGP and LCPO during sintering performed in the manufacture of the solid-state battery 1, and the resulting decomposition of LAGP and LCPO, may occur more easily.

[0044] Therefore, the firing temperature during firing in manufacturing the solid state battery 1 is in the range of less than 900°C, preferably in the range of 600°C or higher and 800°C or lower, and more preferably in the range of 600°C or higher and lower than 800°C.

[0045] Here, a comparison was made between the LAGP sintered body of sample No. 1-2, which had a low sintering temperature of 600°C, and the LAGP sintered body of sample No. 5, which had a high sintering temperature of 800°C. Through the comparison, knowledge was gained about the differences in the oxidative decomposition behavior and material structure (crystallinity) of these LAGP sintered bodies. The comparison and knowledge are described below with reference to Figure 2, Table 2, Figure 3 and Figure 4.

[0046] First, the results of LSV measurements and the knowledge gained from them about the oxidative decomposition behavior are described. FIG. 2 shows an example of the LSV measurement results. FIG. 2 shows the LSV measurement results of the LAGP sintered bodies of samples No. 1-2 and 5. In FIG. 2, the horizontal axis is the voltage (vs. Li / Li + ) [V], and the vertical axis represents the current density [mA / cm 2 Table 2 shows the current density at voltages of 5 V, 5.5 V, and 6 V in the LSV measurements.

[0047] [Table 2]

[0048] From the LSV measurement results in FIG. 2, it can be seen that the LAGP sintered body of sample No. 5, which was fired at a temperature of 800°C, has a tendency for the current density to increase as the voltage increases, i.e., as the voltage approaches the positive electrode side voltage of the solid-state battery 1, compared to the LAGP sintered body of sample No. 1-2, which was fired at a temperature of 600°C.

[0049] From Table 2, the LAGP sintered compact of sample No. 5, which was fired at 800°C, has a higher current density at the positive electrode voltages of 5V, 5.5V, and 6V of the solid-state battery 1, as compared to the LAGP sintered compact of sample No. 1-2, which was fired at 600°C. The LAGP sintered compact of sample No. 1-2, which was fired at 600°C, has a similar current density regardless of whether the firing atmosphere is nitrogen or air.

[0050] In the LAGP sintered body of sample No. 5, which was fired at 800°C, the current density in the voltage range of 5 V to 6 V, which is an example of the positive electrode voltage of solid-state battery 1, was 4.1 × 10 -4 mA / cm 2 On the other hand, in the LAGP sintered body of sample No. 1-2, which was fired at 600° C., the current density in the voltage range of 5 V to 6 V, which is an example of the positive electrode voltage of the solid-state battery 1, is 1.5×10 -4 mA / cm 2 It can be kept below.

[0051] From Figure 2 and Table 2, it can be said that more current flows under positive voltage in the LAGP sintered compact of sample No. 5, which was fired at 800°C, compared to the LAGP sintered compact of sample No. 1-2, which was fired at 600°C. From this, it can be said that the LAGP sintered compact of sample No. 1-2, which was fired at 600°C, can suppress oxidative decomposition under positive voltage more than the LAGP sintered compact of sample No. 5, which was fired at 800°C.

[0052] Next, we will discuss the results of X-ray diffraction and Raman spectroscopy, as well as the findings on the material structure (crystallinity) obtained from them. FIG. 3 is a diagram showing an example of the results of X-ray diffraction measurement. In FIG. 3, the results of X-ray diffraction measurement of the LAGP sintered bodies of Samples No. 1-2 and 5, and the results of X-ray diffraction measurement of amorphous LAGP (Li 1.5 Al 0.5 Ge 1.5 FIG. 4 shows an example of the results of Raman spectroscopy. FIG. 4 shows the results of Raman spectroscopy of the LAGP sintered bodies of samples No. 1-2 and 5, as well as the results of the Raman spectroscopy of amorphous LAGP (Li(PO4)3) before sintering, which is an amorphous solid electrolyte material, as a reference. 1.5 Al 0.5 Ge 1.5 The Raman spectroscopic measurement results of (PO4)3) are shown.

[0053] From the X-ray diffraction measurement results in Figure 3, it was found that the crystalline solid electrolyte material LAGP (Li 1.5 Al 0.5 Ge 1.5 X-ray diffraction peaks due to (PO4)3) appear. Therefore, it can be said that both LAGP sintered compacts of samples No. 1-2 and 5 contain crystalline LAGP. However, the intensity of the X-ray diffraction peaks due to crystalline LAGP is weaker in the LAGP sintered compact of sample No. 1-2, which was sintered at 600°C, than in the LAGP sintered compact of sample No. 5, which was sintered at 800°C. GeO2 is a heterophase that is generated during sintering of amorphous LAGP.

[0054] In addition, the Raman spectroscopy results in Fig. 4 show that for the LAGP sintered body of sample No. 1-2, which was sintered at 600°C, the sintering temperature was 0 cm3 regardless of whether the sintering atmosphere was nitrogen or air. -1 From 1000cm -1 The amorphous solid electrolyte material, amorphous LAGP (Li 1.5 Al 0.5 Ge 1.5 In contrast, in the LAGP sintered body of sample No. 5, which was sintered at 800°C, a broad Raman shift peak due to the amorphous LAGP (Li 1.5 Al 0.5 Ge 1.5 The broad Raman shift peak due to (PO4)3) disappeared, and the crystalline solid electrolyte material LAGP (Li 1.5 Al 0.5 Ge 1.5 Only the peak of the Raman shift due to (PO4)3) appears. Therefore, it can be said that the LAGP sintered body of sample No. 1-2 contains amorphous LAGP, while the LAGP sintered body of sample No. 5 contains little or no amorphous LAGP. GeO2 is a different phase that is generated during the sintering of amorphous LAGP.

[0055] From the X-ray diffraction measurement results in FIG. 3 and the Raman spectroscopy measurement results in FIG. 4, it can be said that the LAGP sintered body of sample No. 1-2, which was fired at 600°C, was not completely crystallized by firing, and had a material structure in which the crystalline phase and amorphous phase of LAGP were mixed.

[0056] In the LAGP sintered compact of sample No. 5, which was sintered at 800°C, the amorphous LAGP crystallized during sintering (Figs. 3 and 4), and the crystallization achieved a relatively high ionic conductivity (Table 1). However, in the LAGP sintered compact of sample No. 5, which was sintered at 800°C, oxidative decomposition occurred relatively easily under positive electrode voltage (Fig. 2 and Table 2).

[0057] In contrast, the LAGP sintered compact of sample No. 1-2, which was sintered at 600°C, has a material structure in which the crystalline and amorphous phases of LAGP are mixed upon sintering (Figs. 3 and 4). The LAGP sintered compact of sample No. 1-2, which was sintered at 600°C, achieves a level of ionic conductivity that can be used as a solid electrolyte for the solid-state battery 1 (Table 1). Furthermore, the LAGP sintered compact of sample No. 1-2, which was sintered at 600°C, is relatively resistant to oxidative decomposition under positive electrode voltage (Fig. 2 and Table 2).

[0058] Therefore, as in sample No. 1-2, by sintering amorphous LAGP at a sintering temperature of 600°C to obtain a material structure in which the crystalline phase and amorphous phase of LAGP are mixed, a solid electrolyte with excellent oxidation resistance and a solid-state battery 1 including such a solid electrolyte are realized.

[0059] Here, the LAGP sintered body of sample No. 1-2, which was sintered at 600°C for 2 hours, is shown as an example of a material structure in which the crystalline and amorphous phases of LAGP are mixed by sintering. In addition, it is possible to obtain a material structure in which the crystalline and amorphous phases of LAGP are mixed by sintering even if the sintering temperature is higher or the sintering time is longer. For example, it is possible to obtain a material structure in which the crystalline and amorphous phases of LAGP are mixed by sintering even if the sintering temperature is in the range of more than 600°C and less than 800°C, or if the sintering time is more than 2 hours.

[0060] Here, we will describe the results of observing the appearance of the LAGP sintered bodies obtained by firing under various conditions. FIG. 5 is a diagram showing an example of the appearance observation result. FIG. 5 shows the results of the appearance observation of seven kinds of LAGP sintered bodies, including the above-mentioned samples No. 1-6 and further sample No. 7, with a microscope. Sample No. 1 is a LAGP sintered body sintered under the conditions of 600°C, nitrogen atmosphere, 2 hours. Sample No. 2 is a LAGP sintered body sintered under the conditions of 600°C, air atmosphere, 2 hours. Sample No. 3 is a LAGP sintered body sintered under the conditions of 700°C, air atmosphere, 2 hours. Sample No. 4 is a LAGP sintered body sintered under the conditions of 700°C, air atmosphere, 20 hours. Sample No. 7 is a LAGP sintered body sintered under the conditions of 780°C, air atmosphere, 2 hours. Sample No. 5 is a LAGP sintered body sintered under the conditions of 800°C, air atmosphere, 2 hours. Sample No. 6 is a LAGP sintered body sintered under the conditions of 900°C, air atmosphere, 2 hours.

[0061] As described above, sample No. 1-2, which was sintered at 600°C for 2 hours, is a LAGP sintered body with a material structure in which the crystalline and amorphous phases of LAGP are mixed. As shown in Figure 5, the appearance of sample No. 1-2 is observed to be uniform regardless of whether the sintering atmosphere is nitrogen or air.

[0062] In contrast, in sample No. 3, which was fired at a higher temperature of 700°C for the same 2 hours, dot-shaped crystalline phases begin to appear at a level that can be recognized by external observation, as shown in Figure 5. In sample No. 4, which was fired at 20 hours but at the same temperature of 700°C, the dot-shaped crystalline phases grow to a level that can be clearly recognized by external observation, as shown in Figure 5. In sample No. 7, which was fired at a higher temperature of 780°C for 2 hours, the crystalline phase grows and becomes the majority, and instead, the amorphous phase remains in the form of dots, as shown in Figure 5. Sample No. 7, which was fired at 780°C, is a LAGP sintered body with a material structure in which the crystalline and amorphous phases of LAGP are mixed.

[0063] On the other hand, sample No. 5, which was fired at 800°C for 2 hours, is a LAGP sintered body with a LAGP crystal phase. In sample No. 5, the crystal phase has grown more than in samples No. 3-4, which were fired at 700°C, and sample No. 7, which was fired at 780°C, and the appearance is observed to be a uniform crystal phase state, as shown in Figure 5. Sample No. 6, which was fired at a higher temperature of 900°C, is observed to be in a uniform state, as shown in Figure 5.

[0064] As shown in FIG. 5 and the above-mentioned FIGS. 3 and 4, at a firing temperature of 800° C., amorphous LAGP changes to crystalline LAGP. As shown in FIG. 5, at a firing temperature of less than 800° C., a material structure in which the crystalline phase and amorphous phase of LAGP are mixed is obtained. As described above, when the LAGP sintered body has a material structure in which the crystalline phase and amorphous phase of LAGP are mixed, it is possible to suppress oxidative decomposition under a positive electrode voltage while ensuring an ionic conductivity that can be used as a solid electrolyte of the solid-state battery 1. In addition, if the firing temperature is relatively low, less than 800° C., it is also possible to suppress the reaction between LAGP and LCPO and the resulting decomposition of LAGP and LCPO during firing performed when manufacturing the solid-state battery 1.

[0065] Therefore, the firing temperature during firing performed when manufacturing the solid-state battery 1 is preferably in the range of 600° C. or higher and lower than 800° C., for example, in the range of 600° C. or higher and 780° C. or lower.

[0066] For example, the solid-state battery 1 can be manufactured as follows. Amorphous LAGP, which is one of the amorphous solid electrolyte materials having a NASICON structure, is prepared. A paste for forming the electrolyte layer 13 containing such amorphous LAGP is prepared. A paste for forming the positive electrode layer 11 containing amorphous LAGP, LCPO as a positive electrode active material, a carbon material as a conductive assistant, etc. is prepared. A paste for forming the negative electrode layer 12 containing amorphous LAGP, TiO2 or Nb2O5 as a negative electrode active material, a carbon material as a conductive assistant, etc. is prepared. Each paste for forming the electrolyte layer 13, the positive electrode layer 11, and the negative electrode layer 12 may contain crystalline LAGP in addition to amorphous LAGP. A paste for forming the cover layer 14 containing an insulating material such as low-melting point glass is prepared.

[0067] Then, the pastes for forming the electrolyte layer 13, the positive electrode layer 11, the negative electrode layer 12, and the cover layer 14 are laminated by printing so as to have a structure as shown in FIG. 1(A). Alternatively, sheets formed by printing from the pastes for forming the electrolyte layer 13, the positive electrode layer 11, the negative electrode layer 12, and the cover layer 14 are laminated so as to have a structure as shown in FIG. 1(A). After lamination, thermocompression bonding, cutting, and the like may be performed. Then, a predetermined heat treatment, that is, a heat treatment (degreasing) for removing organic components in the paste, and further a heat treatment (firing) for sintering the solid electrolyte, glass, and the like are performed. As a result, a battery element 10 having a structure as shown in FIG. 1(A), that is, a battery element 10 including the positive electrode layer 11, the negative electrode layer 12, the electrolyte layer 13, and the cover layer 14 is formed.

[0068] Based on the above findings, the firing temperature during firing when forming the battery element 10 is set to a temperature range of 600°C or more and less than 800°C. By setting the firing temperature to such a temperature range, the amorphous LAGP contained in the electrolyte layer 13, the positive electrode layer 11, and the negative electrode layer 12 before firing changes into a LAGP sintered body having a material structure in which the crystalline phase and the amorphous phase of LAGP are mixed. That is, in the electrolyte layer 13, the positive electrode layer 11, and the negative electrode layer 12 after firing, a LAGP sintered body containing the crystalline phase and the amorphous phase of LAGP is formed from the amorphous LAGP before firing as a solid electrolyte contained therein. Since the LAGP sintered body has a material structure in which the crystalline phase and the amorphous phase of LAGP are mixed, it is possible to suppress oxidative decomposition under the positive electrode side voltage while ensuring a certain level or more of ion conductivity that can be used in the solid battery 1. In addition, by setting the firing temperature to a relatively low temperature of less than 800°C, it is also possible to suppress the reaction of LAGP and LCPO and the resulting decomposition of LAGP and LCPO.

[0069] 1(B), after the battery element 10 is formed, a positive external electrode 20 and a negative external electrode 30 are formed. The external electrode 20 is formed so as to be connected to the positive electrode layer 11 at one end surface 10a of the battery element 10. The external electrode 30 is formed so as to be connected to the negative electrode layer 12 at the other end surface 10b of the battery element 10. The external electrodes 20 and 30 are formed by applying a paste containing Ag or the like and baking it, or by further plating the surface with Ni, Sn or the like.

[0070] The solid-state battery 1 is manufactured by the above-mentioned method. The firing temperature during firing performed when manufacturing the solid-state battery 1 is set to a temperature range of 600°C or higher and lower than 800°C, and a LAGP sintered body containing a crystalline phase and an amorphous phase of LAGP is formed from the amorphous LAGP as a solid electrolyte of the solid-state battery 1. This realizes a solid electrolyte that has an ionic conductivity of a certain level or higher that can be used in the solid-state battery 1 and is suppressed from oxidative decomposition under a positive electrode voltage. Therefore, a solid electrolyte with excellent oxidation resistance and a solid-state battery 1 including such a solid electrolyte are realized.

[0071] Here, as the amorphous solid electrolyte material, amorphous LAGP is exemplified. Further, as the amorphous LAGP, the composition x in the general formula Li 1+x Al x Ge 2-x (PO4)3 where x is 0.5, amorphous Li 1.5 Al 0.5 Ge 1.5 (PO4)3 is exemplified.

[0072] As the amorphous LAGP of the amorphous solid electrolyte material, the composition x in the general formula Li 1+x Al x Ge 2-x (PO4)3 is not limited to x being 0.5, and those having a composition x other than 0.5 in the range of 0 < x ≤ 1 may be used. Even for such an amorphous LAGP having a composition x, by setting the firing temperature in the temperature range of 600°C or higher and lower than 800°C, it is possible to obtain a LAGP sintered body containing a crystalline phase and an amorphous phase, and to realize a solid electrolyte having an ion conductivity of a certain level or higher that can be used in the solid battery 1 and suppressed oxidative decomposition under the positive electrode side voltage.

[0073] Furthermore, as the amorphous solid electrolyte material, it is not limited to amorphous LAGP. For example, various materials containing constituent elements different from LAGP, such as those represented by the general formula Li 1+x Al x Sn y Ge 2-x-y (PO4)3 and those represented by the general formula Li 1+x Al x Ti 2-x (PO4)3, may be used. Even for such an amorphous solid electrolyte material, by setting the firing temperature in the temperature range of 600°C or higher and lower than 800°C, it is possible to obtain a sintered body containing a crystalline phase and an amorphous phase, and to realize a solid electrolyte having an ion conductivity of a certain level or higher that can be used in the solid battery 1 and suppressed oxidative decomposition under the positive electrode side voltage.

[0074] In addition, in the case of sintering an amorphous solid electrolyte material, when the sintering temperature is set to the above-mentioned temperature range of 600°C or more and less than 800°C, the sintering atmosphere and sintering time are not limited to those exemplified in Table 1 above, and can be appropriately set. For example, the sintering atmosphere is not limited to an air atmosphere, and may be a nitrogen atmosphere. Furthermore, the sintering time is not limited to 2 hours or 20 hours. In general, in the sintering of an amorphous solid electrolyte material, the longer the sintering time, the more the formation of a crystalline phase progresses. By appropriately setting the sintering temperature, the sintering atmosphere, and the sintering time, the mixed state of the crystalline phase and the amorphous phase or the crystallinity may be changed or adjusted. [Explanation of symbols]

[0075] 1 solid state battery 10 Battery elements 10a, 10b end face 11 Positive electrode layer 12 Negative electrode layer 13 Electrolyte layer 14 Cover Layer 20, 30 external electrode

Claims

1. Preparing an amorphous solid electrolyte material having a NASICON structure; sintering the amorphous solid electrolyte material at a temperature range of 600° C. or more and less than 800° C. to form a solid electrolyte including a crystalline phase and an amorphous phase from the amorphous solid electrolyte material; A method for manufacturing a solid-state battery, comprising:

2. The amorphous solid electrolyte material is Li 1+x A x Ge 2-x (P.O. 4 ) 3 The method for producing the solid-state battery according to claim 1 , wherein x is an integer of 0 to 1.

3. The method for producing a solid-state battery according to claim 1 , wherein the amorphous solid electrolyte material is fired at a temperature in the range of 600° C. to 780° C.

4. The solid electrolyte has a current density of 1.5×10 in the voltage range of 5 V or more and 6 V or less. -4 mA / cm 2 The method for producing a solid-state battery according to claim 1 , wherein:

5. The solid electrolyte has an X-ray diffraction peak of a crystalline solid electrolyte material when measured by X-ray diffraction, and a Raman shift of 0 cm -1 More than 1000cm -1 The method for producing a solid-state battery according to claim 1 , wherein the Raman shift of the crystalline solid electrolyte material exhibits a broader peak than that of the crystalline solid electrolyte material in the following range:

6. The method for producing a solid-state battery according to claim 1 , wherein the amorphous solid electrolyte material in contact with the positive electrode active material is fired at a temperature in the range of 600° C. or more and less than 800° C.

7. The positive electrode active material is Li 2 CoP 2 O 7 The method for producing the solid-state battery according to claim 6 ,

Citation Information

Patent Citations

  • Solid electrolyte and its formation method

    JP2007305552A

  • All-solid lithium battery

    WO2007004590A1

Cited By

  • Positive electrode-side electrolyte separator, negative electrode-side electrolyte separator, lithium metal battery, and electric device

    CN121076225A

  • Solid electrolyte, electrochemical device, and method for producing solid electrolyte

    JP7934937B1